Strategies and Best Practices of Knowledge Management in Academic Libraries in Nigeria - Awoyemi, Robert Akinade; Okojie, Victoria (Ghana Library Journal, 2024)
Knowledge has become a crucial resource in our society. Managing knowledge (KM) helps information professionals in improving services rendered to library users. The digital era has revolutionised the landscape of KM in academic libraries, presenting new opportunities and challenges for information professionals. Academic libraries face the complex task of formulating effective strategies and implementing best practices for knowledge management. To actively participate in KM activities, certain competencies and skills are required by library personnel. Thus, this study explores knowledge management practices in academic libraries in Nigeria. The study adopted descriptive survey research design. The population of the study consists of 114 library professionals working in the eight (8) academic libraries in Nigeria. The sampling technique adopted for this study was random selection and the main research instrument was a structured questionnaire. The collected data were analysed using descriptive and inferential statistics. Results revealed the main purposes of implementing KM in academic libraries are improving library services, managing information explosions, and meeting information needs of users.  The highest rated areas of KM include digital and online services, reference services and technical services while strategies of KM included providing and using available ICT facilities, training in ICT and KM, and developing a knowledge sharing culture. The benefits of KM include gaining new skills, eradicating duplication of work, and providing new jobs and roles to library professionals. The study recommends that library management needs to make adequate provision for staff training and technological infrastructure to facilitate knowledge management and improve library services.